Therapeutic drug monitoring of mycophenolic acid and clinical outcomes of lupus nephritis: a systematic review and meta-analysis - Wonngarm Kittanamongkolchai; Yingyos Avihingsanon; Suwasin Udomkarnjananun; Natavudh Townamchai; Leelahavanichkul Asada; Thunyatorn Wuttiputhanun; Nuanjanthip Naiyarakseree; Pajaree Chariyavilaskul (Lupus Science and Medicine)
Introduction Mycophenolic acid (MPA) is a primary immunosuppressive agent used in the treatment of lupus nephritis (LN). While therapeutic drug monitoring (TDM) of MPA is well established in organ transplantation, its role in LN treatment remains uncertain. Our objective was to review and summarise current knowledge on TDM of MPA in the LN treatment.Methods A systematic search was conducted in the online databases, specifically targeted patients diagnosed with LN receiving MPA treatment. The included studies had to report both MPA pharmacokinetic parameters and renal outcomes. A random-effects model meta-analysis was conducted to assess the relationship between clinical responses and MPA pharmacokinetics.Results A total of 1507 studies were initially screened, resulting in the inclusion of 16 studies for meta-analysis, encompassing 433 patients. The response group exhibited significantly higher MPA area under the concentration-time curve (AUC) compared with the non-response group (51.44±21.73 mg·h/L vs 30.30±16.24 mg·h/L). The weighted mean difference (WMD) of MPA-AUC between responders and non-responders was 16.83 mg·h/L (95% CI 10.59 to 23.06; p<0.001). Similarly, trough concentration (C0) of MPA showed a strong association with renal response, evidenced by C0 values of 2.50±1.73 mg/L in the response group vs 1.51±1.33 mg/L in the non-response group (WMD 1.37 mg/L; 95% CI 0.77 to 1.97; p<0.001). There was no significant relationship identified between MPA-AUC and adverse events.Conclusion This meta-analysis emphasised the meaningful correlation between MPA AUC and C0 with renal response in LN treatment. Randomised controlled trials are necessary to validate this approach and determine its superiority over fixed dosing in the context of LN treatment.